The Conventional An Tiepileptic Drug Use When Compared To A Combination Therapy Regime In A Teaching Hospital In India - MANISHA NAITHANI; KSHITISH KUMAR KSHITIZ (International Journal of Pharma and Bio Sciences, 2012)
Epilepsy is a common chronic neurological disorder characterized by seizures. The recurrent seizures which pose a significant psychosocial and medical risk to the patient can be prevented by antiepileptic drugs (AED). The majority of patients achieve seizure control by effective monotherapy only. Among the antiepileptics phenytoin, phenobarbitone and carbamazepine remain the stalwarts, either as monotherapy or in combination with other drugs. We tried to determine the pattern of these conventional antiepileptics use, the degree of epileptic control achieved and the therapeutic drug levels achieved by the epileptics in Armed Forces Medical College, Pune. A total of 123 patients attending OPD were randomly included in the study. Phenytoin was found to be the most frequently used AED. Monotherapy was used on 68.3% of subjects. 40 (32.5%) subjects on monotherapy and 12 (9.75%) subjects on polytherapy were free of seizures with the AEDs they were receiving from the clinic. Only 19.5 % of patients achieved therapeutic drug levels measured only for the conventional drugs. This study shows that most of the epileptics can be effectively managed with the conventional AEDs with clinical monitoring with judicious use of monitoring in special circumstances